A Comprehensive Review of Financial Services Management - Kumar, Arpan (Journal of Advanced Research in Service Management, 2023)
Financial Services Management is a multifaceted discipline encompassing various aspects of the financial industry, from traditional banking and insurance to cutting-edge fintech and investment management. This comprehensive review explores the historical evolution, key components, challenges, innovations, globalization, ethical considerations, and future trends within the realm of financial services management. The review begins by providing a historical context, tracing the development of financial services from ancient banking systems to contemporary digital platforms. It highlights the pivotal role of regulations such as the Glass-Steagall Act, Dodd-Frank Act, and Basel Accords in shaping the industry. Key components of financial services management, including banking, insurance, investment management, and financial planning, are thoroughly examined. The rise of fintech, artificial intelligence, and blockchain technology has ushered in a new era of innovation, revolutionizing payment systems, investment strategies, and risk management. Challenges in the financial services sector, including market volatility, cybersecurity threats, and regulatory compliance, are addressed, along with strategies for effective risk mitigation. Ethical considerations and the integration of sustainable finance principles into decision-making processes are emphasized as critical aspects of modern financial services management. The globalization of financial services is explored, highlighting the internationalization of banks and cross-border investments. Lastly, the review delves into future trends, discussing the impact of artificial intelligence, potential regulatory changes, and the growing significance of climate finance. This review serves as a valuable resource for professionals, academics, and enthusiasts seeking a comprehensive understanding of the dynamic field of Financial Services Management and its profound impact on the global economy.